Effects of congested fixture and matches` participation on internal and external workload indices in professional soccer players - Rodrigues Garcia, G.; Gonçalves, L. G. C.; Clemente, F. M.; Nakamura, F. Y.; Nobari, H.; Souza Bedo, B. L.; Azevedo, A. M.; Guerra Jr, M. A.; Aquino, R. (Scientific Reports, 2021)
This study aimed to verify the effects of congested fixture and matches` participation on internal and external workload indexes in professional Brazilian soccer players. Rate of perceived exertion-based training load (sRPE), distance- and accelerometry-based measures were daily monitored over 119 training sessions and 33 matches performed by 29 male outfield players. Weeks were classified as congested (n = 11, two or more matches within a 7-day period) and regular (n = 10, one match or less within a 7-day period). The players were divided based on the matches` participation: (1) players who played = 60 min (G1); (2) players who played < 60 min (G2); (3) players who did not participate of the match (G3). The findings showed that independent of the levels of participation during the matches, regular weeks presented greater acute, monotony, and strain indices for internal and external workload measures than congested weeks. The G1 presented the highest values for most of the workload indices in both regular and congested weeks, except for monotony indices (internal and external load) that G2 showed greater values than G1 and G3. Coaches and practitioners should plan the training "doses" to reduce disparities of these different match`s participation and congested schedule weeks.